A latent class segmentation analysis of gamblers in a gambling destination. (June 2020) - Li, Jun (Justin); Bonn, Mark; Kim, Jong-Hyeong
Abstract: Gambling plays an important role in attracting tourists to destinations and significantly contributes to local economies through the generation of salaries and employment supported by visitor spending. Perceptions of value associated with the gambling experience, the gambling facility and the destination, along with the overall level of satisfaction with the visit and willingness to return, represent important categories of consumer information that must be obtained by marketing professionals to maximize opportunities for success in the highly competitive marketing environment. An exhaustive literature review confirmed few studies have investigated perceived value in a satisfaction-intention relationship framework involving visitor segmentation research. Data obtained from 409 gamblers were employed to segment consumers into four mutually exclusive groups based upon their perceived values, satisfaction, and likelihood of returning. Findings offer unique opportunities for gambling destination marketers to identify plausible target audiences and develop differentiated consumer relationship strategies based upon specific segments. Highlights: Explores the potential existence of heterogeneity among gamblers. Investigates perceived value in a satisfaction-intention relationship framework. Segments the gamblers into four mutually exclusive groups.